Pengumuman Dividen Tunai terhadap Return Saham - Silvie Dwi Jayanti (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2019)
This study aimed to examine the information content of the announcement of dividend distribution that can be reflected by the abnormal return arising from market reaction. Announcement of dividend distribution is divided into dividends increases and dividend decreases. The market reaction can be measured by using abnormal return as the value of the price change. This study using event study approach and observation of the abnormal return for 21 days, 10 days before the announcement, one day at the time of the announcement and 10 days after the announcement. This study uses secondary data obtained from the Indonesia Stock Exchange. This study used a sample of 43 companies comprising of 26 companies that pay cash dividends increases and 17 companies that pay cash dividends decreases. Samples were taken by using purposive sampling method. The data used in this study includes data of companies that pay cash dividends that are listed in the stock group LQ 45 period February 2014 to January 2015. To calculate the expected return using the Market Adjusted Model. The statistical tool that researcher use is one sample t-test, paired sample t-test and independent sample t-test. The results of this study indicate that (1) There is a significant abnormal return in the dividend announcement from company that increasing dividend on t-7, t-2, and t0 all reacted positively while for the company that decreasing dividend there is also a significant abnormal return on a t-7, t0, & t+3 all of which reacts negatively with a significance level of 10%. (2) There is a difference of abnormal return before and after the dividend announcement for company that increasing dividend and there is no difference of abnormal return before and after the dividend announcement for a company that decreasing dividend.(3) There is a difference of abnormal return before the dividend announcement for a company that increasing dividend and for a company that decreasing dividend and (4) There is no difference of abnormal return after the announcement dividend for company that increasing dividend and for company that decreasing dividend. So it can be conclude investors react in the moments before the announcement of the dividend, reacted positively to the dividend increases and reacted negatively to dividend decreases.